The Adolescent in Family Therapy : breaking the cycle of conflict and control - Micucci, Joseph A. (New York : The Guilford Press, 1998)
Presenting a developmentally grounded approach to treating a wide range of adolescent problems, Joseph Micucci shows how troubled teenagers and their parents can be helped to use family relationships as catalysts for growth and change. Filled with realistic case examples, practical discussions of the process of assessment and therapy, and straightforward clinical advice, The Adolescent in Family Therapy is a valuable addition to the library of readers at many different levels of expertise.
Integrating ideas from many different models of family therapy, this clearly written book will be useful to all therapists working with troubled teenagers, including family therapists, social workers, psychologists, and psychiatrists. It also serves as a primary or supplemental text for graduate-level courses on psychotherapy with adolescents, family therapy theory and practice, adolescent development, and child and adolescent psychopathology.
Ch. 1. Introduction -- Ch. 2. The Process of Therapy: Principles and Pitfalls -- Ch. 3. Adolescent Development -- Ch. 4. Eating Disorders -- Ch. 5. Depression and Suicide -- Ch. 6. Violence, Delinquency, and Other Problem Behaviors -- Ch. 7. Psychosis -- Ch. 8. Underachievement and Other School-Related Problems -- Ch. 9. Problems of "Leaving Home" -- Ch. 10. Multiproblem Families -- Epilogue: The ARCH.
Includes bibliographical references (p. 307-323) and index (p. 325-336).
Keywords: Adolescent psychotherapy; Family psychotherapy; Families -- Psychological aspects; Parent and teenager